Pancoast Tumor: A Rare presentation of Hepatocellular Carcinoma - Khan, Enam Murshed; Sutradhar, Arpita (Annals of Pathology and Laboratory Medicine, 2019)
Lung is the first most common site for metastasis of hepatocellular carcinoma. Pancoast’s tumor is usually caused by adenocarcinoma of lung. Hepatocellular carcinoma is very notorious in remaining asymptomatic for prolonged time. But metastatic Hepatocellular carcinoma presenting as apical lobe lung mass eroding the ribs (Pancoast’s tumor) is unusual. We, describe here a 66year old male who presented with left shoulder pain which was subsequently diagnosed to be due to metastatic tumor of upper lobe lung from liver primary. To our knowledge Pancoast’s syndrome due to metastatic hepatocellular carcinoma is rare and only two cases have been reported previously to the best of our knowledge. This case report will allow the clinicians to consider metastatic HCC as a differential for Pancoast’s tumor.